Oxygen transfer rate in an aerated tank for pharmaceutical wastewater treatment - Ghasem D. Najafpour; Lee , Chiah Lin (2002)
The treatment of pharmaceutical non-penicillin wastewater was conducted in the biological aerobic process. The oxygen transfer rate played the major role to reduce the organic pollutants of the wastewater by removing gases, oils, volatile acids and odour. The microbial culture used in the experiment was the ethanol producers, isolated from the wastewater: Optical density, COD and concentration of chemicals equivalent to carbohydrate were measured in a time period of 3-4 days of aeration. The propagation of bacteria was monitored and its growth rate was determined. Oxygen transfer rate and mass transfer coefficients were found to be affected by airflow rate, bubble size and agitation rate. Dissolved oxygen was shown as an indication of microbial growth and limitation of mass transfer: The dissolved oxygen was about 7.89 ppm from the starting point and then it dropped to 2 ppm by the end of the first day. After the second day of aeration the oxygen depletion was obviously observed since the DO meter showed 0.14 ppm. Aeration rate was 0.2 - 1.3 liters per minute for working volume of 3 liters and 5-10 liters per minute for 15 liters aerated tank. Maximum optical density was obtained with high aeration rate at the first day of aeration, 0.95 g/l, as the aeration was reduced the cell propagation was also reduced. The maximum cell growth was obtained by the end of 3 days of aeration with minimum airflow rate. The maximum COD and carbohydrate reduction was 58 and 90 percent respectively with 1.15 liter/min airflow rate in the 3 liters aeration system. The bubble size affected the mass transfer coefficient (KLa), as the contact surface of gas exposure to liquid increased the mass transfer coefficient was increased. As the dissolved oxygen concentration dropped the KLa was also decreased. The values of KLa for the 5 and 10 liters/min airflow rate for 15 liters aerated tank were 0.055 h- 1 and 0.3975 h-1 respectively